Analisis Prediksi Kebangkrutan Pada Perusahaan Tekstil Dan Garmen Periode 2022-2024 - Pertiwi, Intan Putri; Wuriasih, Anik; Parastri, Desirianingsih H. (ACE: Accounting Research Journal, 2025)
This study aims to analyze and compare the accuracy of five bankruptcy prediction models: the Altman Z-Score, Springate S-Score, Zmijewski X-Score, Grover G-Score, and Taffler T-Score, for textile and garment companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. This study uses quantitative descriptive and comparative methods with secondary data from the financial statements of 18 companies, representing 54 observations. The analysis was conducted through calculating financial ratios for each model, the Kruskal–Wallis test, and accuracy testing. The results show differences in accuracy between the models. The Zmijewski model had the highest accuracy of 92.59% with a 7% error rate, followed by Grover (77.78%), Taffler (74.07%), Altman (72.22%), and Springate (46.30%). Thus, the Zmijewski model is considered the most effective in predicting potential bankruptcy in the textile and garment industry in Indonesia.